2016
DOI: 10.1038/ncomms12971
|View full text |Cite
|
Sign up to set email alerts
|

Forward design of a complex enzyme cascade reaction

Abstract: Enzymatic reaction networks are unique in that one can operate a large number of reactions under the same set of conditions concomitantly in one pot, but the nonlinear kinetics of the enzymes and the resulting system complexity have so far defeated rational design processes for the construction of such complex cascade reactions. Here we demonstrate the forward design of an in vitro 10-membered system using enzymes from highly regulated biological processes such as glycolysis. For this, we adapt the characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 58 publications
(60 reference statements)
0
65
0
4
Order By: Relevance
“…There is increasing interest in natural product biosynthesis as a source of new antimicrobials, human therapeutics, and fine chemicals. The synthetic biochemistry platform, which allows the rapid optimisation of pathway flux 12,57 using purified enzymes from different sources to identify high yielding combinations, is a powerful tool for natural product biosynthesis. Potentially, it could be used as a drug discovery tool, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is increasing interest in natural product biosynthesis as a source of new antimicrobials, human therapeutics, and fine chemicals. The synthetic biochemistry platform, which allows the rapid optimisation of pathway flux 12,57 using purified enzymes from different sources to identify high yielding combinations, is a powerful tool for natural product biosynthesis. Potentially, it could be used as a drug discovery tool, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In our case, we obtained 61 mg L −1 raspberry ketone in a batch system, which is approximately 10-fold higher than the highest reported concentration from fermentation. Further improvement could also be achieved with a continuous flow system such as that reported recently by Hold et al 57 for active provision of substrates and removal of product. Moreover, during our optimisation experiments, we identified that high concentrations of tyrosine as the starting substrate inhibited the overall yield of raspberry ketone.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as the dynamic parameters of enzymes vary a lot under different conditions, such as pH and buffer components, the modeling strategies depend on the parameters which are obtained from specific condition and can hardly be accurate. To overcome this limitation, Panke and coworkers applied an approach based on classical engineering systems theory for optimization of their dihydroxyacetone phosphate (DHAP) producing system (Hold et al, 2016). By characterizing their 10-enzyme system in a continuous stirred tank reactor (CSTR), assisted by an online electrospray ionization mass spectrometry, a sufficiently detailed response of the system to the dynamic challenges was recorded.…”
Section: Tandem Enzymatic Reactionsmentioning
confidence: 99%
“…The in vitro (cell-free) synthetic biology platform comprised of numerous (i.e., more than four) purified enzymes in one vessel or called systems biocatalysis has been proposed to become an emerging biomanufacturing platform (Bujara et al, 2011;Fessner, 2015;Fessner and Walter, 1992;Guterl et al, 2012;Hodgman and Jewett, 2012;Hold et al, 2016;Krutsakorn et al, 2013;Opgenorth et al, 2016;Pardee et al, 2016;Rollin et al, 2015;Tessaro et al, 2015;Zhang et al, 2017;Zhu et al, 2014). Beyond whole-cell constraints, such as, cell membrane, bioenergetics, complicated regulation, and so on, this biomanufacturing platform features high product yields (Opgenorth et al, 2016;Rollin et al, 2015;Zhu et al, 2014), fast reaction or biomanufacturing rates Pardee et al, 2016;Zhu and Zhang, 2017;Zhu et al, 2014), easy process control and optimization (Hold et al, 2016;Opgenorth et al, 2016;Zhu and Zhang, 2017), biosystem robustness (Hodgman and Jewett, 2012;Zhu and Zhang, 2017), great biosystem flexibility (Zhu and Zhang, 2017), easy product separation Satoh et al, 2003), implementation of non-natural reactions and pathways You et al, 2013), and so on. However, there are no commercial production examples based on this platform.…”
Section: Introductionmentioning
confidence: 99%